2013
DOI: 10.1590/s0004-27302013000900013
|View full text |Cite
|
Sign up to set email alerts
|

The unusual association of Graves' disease, chronic spontaneous urticaria, and premature ovarian failure: report of a case and HLA haplotype characterization

Abstract: SUMMARYChronic spontaneous urticaria (CSU), defined as the occurrence of spontaneous wheals for more than six weeks, has been associated with autoimmune diseases. Herein, we report the unusual association of CSU, Graves' disease, and premature ovarian failure. Human leukocyte antigen (HLA) studies were performed. A 36-year-old woman presented symptoms and signs of hyperthyroidism for three months. In the same period, the patient complained of widespread urticarial wheals, intensely itchy, and poorly responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Finally, authors found that treatment of hypothyroidism, like the administration of levothyroxine, was strongly correlated with an improvement in urticaria symptoms [26]. A similar effect was also shown in a report of chronic urticaria and Graves' disease, in which the improvement of hyperthyroidism was correlated with a marked improvement in urticaria symptoms [29]. Kolkhir et al concluded their research speculating about possible pathogenic mechanisms that may sustain their findings, including that IgG thyroid autoantibodies may enhance mast cells' susceptibility to other activating signals [30]; IgE thyroid autoantibodies may induce formation of immune complexes and subsequent activation of the complement that may trigger urticaria [26,31,32].…”
Section: Associations With Other Autoimmune Diseasessupporting
confidence: 58%
“…Finally, authors found that treatment of hypothyroidism, like the administration of levothyroxine, was strongly correlated with an improvement in urticaria symptoms [26]. A similar effect was also shown in a report of chronic urticaria and Graves' disease, in which the improvement of hyperthyroidism was correlated with a marked improvement in urticaria symptoms [29]. Kolkhir et al concluded their research speculating about possible pathogenic mechanisms that may sustain their findings, including that IgG thyroid autoantibodies may enhance mast cells' susceptibility to other activating signals [30]; IgE thyroid autoantibodies may induce formation of immune complexes and subsequent activation of the complement that may trigger urticaria [26,31,32].…”
Section: Associations With Other Autoimmune Diseasessupporting
confidence: 58%
“…6,23,27 Certain HLA types have been found to be associated with POI. 51,52 In addition to HLA, a wider role for immune function genes is suggested. 23 Pathway analysis identified the genes IL11, NLRP11, and PRRC2A (BAT2) near signals for age at menopause in a GWAS in 2012, 23 with NLRP11 also identified as a potential candidate by the most recent GWAS.…”
Section: Immune Functionmentioning
confidence: 99%
“…Her laboratory investigations revealed abnormal HLA haplotypes. Although her serum anti-ovarian antibody titer was negative, the authors concluded the presence of autoimmune ovarian failure and a diagnosis of APS [13].…”
Section: Autoimmune Polyglandular Syndrome (Aps)mentioning
confidence: 97%